Enhancing engineering students’ satisfaction with online learning: factors, framework, and strategies - Al-Khatib, Maryam; Alkhatib, Amira; Talhami, Mohammed; Kashem, Abdurahman Hafez Mohammed; Ayari, Mohamed Arselene; Choe, Pilsung (Frontiers in Education, 2024)
Recently, the learning experience has changed significantly, such as with the use of advanced technology and online lectures to tackle challenges like pandemics. The online learning environment affects students' experiences and depends on various factors, especially for those in fields like engineering, where hands-on classes are crucial for successful learning. This study aims to explore the key factors that affect engineering students' satisfaction with online learning. Based on these factors, we developed a framework to improve students' satisfaction with online learning through a structured survey of students who experienced both in-person learning before the pandemic and online learning during the pandemic. The survey was distributed to 263 students in various engineering disciplines and academic levels to ensure valid results across different groups. Using factor analysis, the results reveal that interactions, services, and technology are the main factors that positively influence online learning. In addition, a multiple linear regression analysis showed that students' satisfaction with online learning depends significantly on the availability and quality of online learning services, assessment and interaction tools, and technology. This study highlights important factors that enhance engineering students' satisfaction with online learning and offers strategies for educators to improve online learning environments, emphasizing the importance of quality services, assessment, and interaction tools.